CCR5 Targeted Cell Therapy for HIV and Prevention of Viral Escape - Hütter, Gero; Bodor, Josef; Ledger, Scott; Boyd, Maureen; Millington, Michelle; Tsie, Marlene; Symonds, Geoff (Viruses, 2015)
Allogeneic transplantation with CCR5-delta 32 (CCR5-d32) homozygous stem cells in an HIV infected individual in 2008, led to a sustained virus control and probably eradication of HIV. Since then there has been a high degree of interest to translate this approach to a wider population. There are two cellular ways to do this. The first one is to use a CCR5 negative cell source e.g., hematopoietic stem cells (HSC) to copy the initial finding. However, a recent case of a second allogeneic transplantation with CCR5-d32 homozygous stem cells suffered from viral escape of CXCR4 quasi-species. The second way is to knock down CCR5 expression by gene therapy. Currently, there are five promising techniques, three of which are presently being tested clinically. These techniques include zinc finger nucleases (ZFN), clustered regularly interspaced palindromic repeats/CRISPR-associated protein 9 nuclease (CRISPR/Cas9), transcription activator-like effectors nuclease (TALEN), short hairpin RNA (shRNA), and a ribozyme. While there are multiple gene therapy strategies being tested, in this review we reflect on our current knowledge of inhibition of CCR5 specifically and whether this approach allows for consequent viral escape.
Keywords: receptory HIV; Stem Cell Transplantation; Biological Therapy; Receptors, CCR5; HIV Infections; lidé; Gene Knockdown Techniques; HIV-1; transplantace kmenových buněk; tropism; gene therapy; HIV infekce; Receptors, HIV; CCR5; CCR5-delta32; genový knockdown; viral escape; chemokine receptor; receptory CCR5; biologická terapie; Humans